ANALISIS YURIDIS SISTEM E-COURT DAN E-LITIGASI PADA CERAI GUGAT BEDA KEWARGANEGARAAN DI PENGADILAN AGAMA (STUDI PUTUSAN NO. 309/Pdt.G/2020/PA.Btg DAN NO. 313/Pdt.G/2021/PA.Dps) - Suardi, Suardi; Alfitri, Alfitri; Darmawati, Darmawati (Ekonomi Syariah STAI Sangatta Kutai Timur, 2022)
This paper was appointed by the author to find out and analyze the problems faced by the judges of the Religious Courts in resolving divorce cases from different countries, to find out and analyze the basic considerations and legal basis used by the panel of judges in resolving the case. The results of this study are as follows: (1) Constraints in the delivery of letters, due to the very far distance from the Defendant's residence. Therefore, the application of the e-litigation system is needed to solve the problems faced by the judges of the Religious Courts in handling divorce cases against different nationalities. Although the e-litigation system still requires evaluation from the Supreme Court regarding the registration process where the parties are required to attend the trial, this is because e-litigation registration can only be done after the mediation process fails. While the mediation process requires the presence of both parties. (2) The Verstek decision handed down by the panel of judges in deciding the divorce lawsuit with case numbers 309/Pdt.G/2020/PA.Btg and number 13/Pdt.G/2021/PA.Dps, in general, has been fully fulfilled. This was due to the absence of the Defendant during the trial. On the other hand, this Verstek decision is to realize the achievement of the principle of justice, which is carried out quickly and at low cost.